The Relationship between COVID-19 Infection and Body Mass Index - Ul Hadi Jawad, Shahbaa Hussien Abd; Eawadah Sahib, Khulud Sabah; Mahmoud, Diana Thaar Obaes; Jasem Ahmed, Nada Ahmed; Salman Dawood, Sukeina Ryad (American Journal of Biology and Natural Sciences, 2024)
Studies have indicated the reasons for considering obesity a risk factor for COVID-19 patients, and have only monitored the statistical relationship between obesity and risk factors due to the disease. Scientists have confirmed that: “The negative effects of obesity come from the fact that it impedes the movement of the diaphragm, which affects ventilation in the lungs. It may also impede immune reactions when infected with the disease, and trigger what is known as (oxidative stress processes), which have a negative effect on cardiovascular function.